Embedding post‐doctoral clinical academic careers in practice: The St Bartholomew's Hospital model. Issue 3 (20th January 2021) - Sanders, Julie; Malcolmson, James; Philpott Jones, Samantha; Kelly, Jonathan
Abstract: Aims and Objectives: In order to retain and develop pre‐doctoral and doctoral staff, we sought to establish and implement a model for supporting postdoctoral clinical academic careers at our hospital. Background: Doctorally‐prepared nurses can raise clinical practice standards, but there is a deficit of career opportunities and post‐doctoral positions. This will inevitably impact delivering the evidence for improving patient outcomes and service delivery. It is therefore imperative that post‐doctoral nursing and allied professional post‐doctoral clinical academic career opportunities are developed and embedded in practice. Design: We describe the development and implementation of a model to provide and embed post‐doctoral clinical academic roles at our hospital. Methods: A multidisciplinary group devised the model which was approved by the Hospital Executive Board. Results: The model includes having a bespoke plan for each individual, planning the post‐doctoral role at time of PhD planning, providing 1 day a week protected research time for a minimum of 12 months after PhD completion, having an appropriate honorary academic contract at a partner University, and providing integrated clinical and academic supervision throughout. Other key components include senior clinical and Executive Board support and an existing vibrant research culture at our organisation. Conclusions: The St Bartholomew's Hospital model, focusing on individualised posts integrating clinical and academic roles to address service needs, offers a novel approach to supporting post‐doctoral clinical academic careers in a clinical setting. Relevance to clinical practice: Since doctorally‐prepared nurses can raise clinical practice standards we developed a sustainable infrastructure to increase our postdoctoral nursing and allied professional workforce. This model could provide a framework for other hospitals to embed postdoctoral clinical academic careers in practice.